THE PREDICTORS OF POTENTIAL DRUG-DRUG INTERACTIONS AMONG DIABETIC HYPERTENSIVE ADULT OUTPATIENTS IN A KENYAN REFERRAL HOSPITAL - LATI, MAKITE SIMON; DAVID, NYAMU GITONGA; KINUTHIA, ROSALINE NJERI (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To characterize the predictors of potential drug-drug interactions among adult diabetic hypertensive outpatients at Kenyatta National Hospital. Methods: This cross-sectional study collected and analyzed data on potential drug interactions from 104 diabetic hypertensive outpatients (aged ≥18 y) at the Department of Endocrinology Outpatient Clinic of Kenyatta National Hospital from 1st May 2019 to 31st August 2019. The main outcome measure was the prevalence of potential drug-drug interactions and their predictors among the study population. Results: There was a female preponderance (70.2%). The mean age of the study participants was 61.6 y (SD±10.8). The prevalence of potential drug interactions was high at 57.7%. The average number of drug interactions was one interacting pair per patient, with a majority of the prescriptions (81.0%) having moderate drug-drug interactions. Patients receiving>2 drugs were almost three times more likely to have drug-drug interaction compared to those prescribed ≤ 2 drugs (AOR=2.79; 95% CI: 1.11-7.28); p=0.029). Participants who were at stage 4 of hypertension were 2.5 times more likely to have a drug-drug interaction compared to the other stages of hypertension (AOR=2.52; 95% CI 1.31-4.89; p=0.007). Conclusion: Polypharmacy and stage 4 hypertension are independently associated with drug-drug interactions among patients with both diabetes and hypertension. Future studies should characterize the specific type of drug interactions and possible targets of minimization of drug-drug interactions.